2021
DOI: 10.1177/00220345211037248
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Fibrocartilage Stem Cells via TNF-α/Nf-κB in TMJ Osteoarthritis

Abstract: In this study, we investigate harnessing fibrocartilage stem cell (FCSC) capacities by regulating tumor necrosis factor α (TNF-α) signaling for cartilage repair in temporomandibular joint osteoarthritis (TMJOA). Stem cell specifics for FCSCs were characterized in the presence of TNF-α. Etanercept as a TNF-α inhibitor and BAY 11-7082 as an Nf-κB inhibitor were used to study TNF-α regulation of FCSCs. Lineage tracing was performed in Gli1-CreERT+;Tmfl/fl mice when etanercept (1 mg/kg, every 3 d) or isometric veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…TNF-α is a key factor in the pathogenesis and progression of osteoarthritis, and its level is increased in chronic inflammatory environment . This proinflammatory factor can regulate nuclear factor-κB pathway, enhance the releasing of matrix metalloproteinases such as MMP3 and MMP13, and impair chondrogenesis, therefore resulting in articular cartilage degradation in the development of TMJ osteoarthritis . Meanwhile, TNF-α is reported to contribute to cell aging, partially via the formation of oxidative stress .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α is a key factor in the pathogenesis and progression of osteoarthritis, and its level is increased in chronic inflammatory environment . This proinflammatory factor can regulate nuclear factor-κB pathway, enhance the releasing of matrix metalloproteinases such as MMP3 and MMP13, and impair chondrogenesis, therefore resulting in articular cartilage degradation in the development of TMJ osteoarthritis . Meanwhile, TNF-α is reported to contribute to cell aging, partially via the formation of oxidative stress .…”
Section: Resultsmentioning
confidence: 99%
“…42 This proinflammatory factor can regulate nuclear factor-κB pathway, enhance the releasing of matrix metalloproteinases such as MMP3 and MMP13, and impair chondrogenesis, therefore resulting in articular cartilage degradation in the development of TMJ osteoarthritis. 43 Meanwhile, TNF-α is reported to contribute to cell aging, partially via the formation of oxidative stress. 44 Intriguingly, MMP3, MMP13, and TNF-α are typical members of SASP, thus linking the proinflammatory and senescence-inducing effects of TNF-α.…”
Section: In Vitro Anti-inflammation and Antisenescence Functions Of P...mentioning
confidence: 99%
“…Apart from this, other factors such as platelet derived growth factor, epidermal growth factor, interleukin-1, and tumor necrosis factor alpha also have role in proliferation, production of collagen, and glycosaminoglycans (GAG) [61]. In a recent study, Chen et al reported inhibition of TNF-α/Nf-κB promoted fibrocartilage stem cell's chondrogenic potential [62]. Kang et al in their study reported that TGF-β1 and IGF-1 induced increase in type 1 collagen and GAG synthesis and cells proliferation [63].…”
Section: Cell Sources and Growth Factorsmentioning
confidence: 99%
“…Some studies develop PLGA-based microparticle formulations to carry anti-inflammatory RNAs to extend their residence time in the TMJ cavity ( Mountziaris et al, 2011 ). Tumor necrosis factor-α (TNF-α) is a kind of pro-inflammatory cytokines, which is expressed highly in the arthritic TMJs ( Bi et al, 2022 ). Mountziaris et al (2011) developed a TNF-α siRNA-PEI-PLGA microparticles and investigated their release kinetics.…”
Section: Intra-articular Drug Delivery Systemsmentioning
confidence: 99%